2017
DOI: 10.1073/pnas.1607541114
|View full text |Cite
|
Sign up to set email alerts
|

Superresolution imaging reveals activity-dependent plasticity of axon morphology linked to changes in action potential conduction velocity

Abstract: Axons convey information to nearby and distant cells, and the time it takes for action potentials (APs) to reach their targets governs the timing of information transfer in neural circuits. In the unmyelinated axons of hippocampus, the conduction speed of APs depends crucially on axon diameters, which vary widely. However, it is not known whether axon diameters are dynamic and regulated by activity-dependent mechanisms. Using time-lapse superresolution microscopy in brain slices, we report that axons grow wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
118
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 44 publications
8
118
0
2
Order By: Relevance
“…3f, j ). Given that axons can be small caliber with bouton sizes that are hundreds of nanometers 31 , diffraction limited LM may confuse neighboring axons, leading to synapse assignment mistakes.…”
Section: Resultsmentioning
confidence: 99%
“…3f, j ). Given that axons can be small caliber with bouton sizes that are hundreds of nanometers 31 , diffraction limited LM may confuse neighboring axons, leading to synapse assignment mistakes.…”
Section: Resultsmentioning
confidence: 99%
“…(slightly) with activity (Chéreau et al, 2017), although this has not been demonstrated at the AIS. It 665 may also change on longer time scales, particularly during development (Leterrier et al, 2017).…”
mentioning
confidence: 86%
“…For example, unmyelinated axons were recently observed to be dynamically regulated 389 by both high-frequency and physiological firing ex vivo, wherein increased activity led to a progressive 390 enlargement of axons in diameter over tens of minutes (Chereau et al, 2017) (Figure 1). Interestingly, 391 axon diameter is now known to be a core determinant of myelination in the CNS (Almeida et al, 2011; 392…”
mentioning
confidence: 99%